Hakikat dan Konsep-Konsep Dasar Psikologi Pendidikan, Belajar dan Pembelajaran Serta Faktor-Faktor yang Mempengaruhinya - Rusdi Rusdi (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2014)
Is a must for every educator who is responsible, that he was in carrying out his duties,act in a manner consistent with the \"state\" of the students. In this context, the role of psychology as a scienceknowledge which seeks to understand human beings, with the goal to be able to treat it with moreright. Therefore, the psychological knowledge of students in the educational process is necessary andimportant for every educator; so that every educator should be a requirement to have knowledgeon educational psychology. The central issue in educational psychology is a matter of learning andlearning. This is not surprising, because the actual teaching and learning is a follow implementationin business education. In seeking to educate, children students learn and the teachers do the teachingto the students. The quality of students' learning outcomes are determined by the learning process that caninfluenced by many factors, both internal and external.